Improved random aggregate model for numerical simulations of concrete engineering simulations of concrete engineering - Yuan, Qin; Junrui, Chai; Faning, Dang (Journal of Civil Engineering and Management, 2013)
In numerical simulations, concrete is usually considered as a three-phase material consisting of an aggregate, a cement matrix, and an interfacial transition zone (ITZ). Three-dimensional modeling of concrete usually requires extremely large computational requirements. In this study, an improved random aggregate model for numerical simulations of concrete is developed, which can minimize the number of elements, optimize the ITZ thickness, and create internal cracks and holes. Numerical investigations on the cracks form as well as deflection and tensile strength are also conducted based on three-point bending tests. The simulation results agree well with the experimental results.